(untitled) (Repertorio Científico, 2022)
As global biodiesel production increases, there is an urgent need to find new applications for consuming glycerin. Biodiesel production in Costa Rica was around 4,5 million liters for 2019, while the installed capacity is 104,4 million liters per year. It is estimated that the potential to generate glycerin as a by-product in Costa Rica is 38 280 - 51 480 kg per month, which is equivalent to 460 - 620 thousand kg of glycerin per year. In other words, only about 4,31% of the installed capacity is being used. Companies do not follow production models that enhance the value of glycerin within their production processes. Therefore, the study of alternatives for the synthesis of compounds of interest from glycerin are an opportunity to boost the Costa Rican chemical industry and the production of biofuels.